The Comparative Analysis of Business Applications for MSMEs based on Android (Case Study on Buku Kas and Buku Warung Applications) - Anisa Septiana; Yeni Priatnasari; Dewi Kartika (Jurnal Riset Akuntansi Terpadu, 2021)
The purpose of this research was to compare the Android-based MSME financial bookkeeping application based on the criteria for a quality accounting application. The used data collection were observation, questionnaires and literature study. The data analysis technique used was descriptive quantitative and comparative analysis. The results of the analysis of each application show that Buku Kas  and  Buku Warung applications have different completeness. The results of the analysis of the research show that in a comparative assessment by respondents from the questionnaire obtained the results that Buku Kas application get a total score of 2.845 while Buku Warung application get a total score of 2.764. The total score shows that 51% of respondents prefer Buku Kas application as an Android-based MSME financial bookkeeping application compared to Buku Warung  application. The conclusion is that there is Buku Kas application has better criteria as an MSME financial bookkeeping application than Buku Warung application.